The Development of the Teacher's Personality in the Process of Pedagogical Activity - Т V Vorontsova; Yu V Sokolova (Peoples' Friendship University of Russia (RUDN University), 2008)
The article analyzes the scientific directions of studying the problems of development of the teacher's personality. The groups of properties describing professionally significant qualities of the teacher, allocated by various scientific schools are considered in the article. It is concluded that personal psychological and pedagogical growth of the teacher as a result of professional work transfers into his individual style of creative activity.